SELF-MANAGEMENT BEHAVIOR AND ITS IMPACT TO GLYCATED HEMOGLOBIN AMONG CLIENTS MEDICALLY DIAGNOSED WITH DIABETES MELLITUS: A CORRELATIONAL STUDY - Somsak Thojampa; Joel Rey Ugsang Acob (Belitung Raya Foundation, Indonesia, 2020)
Background: The Center for Disease Control and Prevention in 2016 identified and further classified Diabetes Mellitus as one of the chronic diseases, a leading cause of morbidity, and considered a major health problem in the Asia Pacific. Hence the quality of life as the optimum goal of any person is only achieved through appropriate self-care management. The person is a major key player of the nursing paradigm plays a crucial task in self-care since his/her responsibility is to assure balance between behavioral and environmental dynamics. Objective: To examine the self-management behaviors of clients medically diagnosed with Diabetes Mellitus and evaluate the correlation between self-management behaviors and glycated hemoglobin (HbA1c). Methods: The study utilized the validated Diabetes Self-Management Questionnaire (DSMQ) tool to 600 adults from the lower district of Khong Khlong, Kamphaengphet, Thailand. Through descriptive design, the investigation focused on major behavioral categories such as glucose management, physical activity, health care use and dietary control on at-risk stroke clients with DM aging 35 years old and above. Respondents with absolute complications of Diabetes Mellitus like stroke, blindness, undergoing dialysis even amputation are excluded to participate. Results: The findings revealed that most clients with DM are married female, ages 51-60 years old and is diagnosed of living with the disease for 6-10 years. Further, the respondents are generally aware on self-management activities for DM, however not all of them submitted for glucose monitoring program. On one hand, the respondents have high regard on controlling dietary intake to avoid the increase of blood glucose during scheduled tests while results also show that most of the respondents are having poor engagement on physical activities. Conclusion: It is concluded that self- management behaviors are strongly associated with HbA1c. Nonpharmacologic and identified independent nursing actions proven to aid clients with diabetes mellitus should be advocated in combating the disease.